IoT-Based Electricity Theft Detection System (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2025)
Globally, energy sectors face the problem of electricity theft, which causes substantial financial losses, inefficiencies, and unpredictability in the energy supply. It involves the unauthorized use of electrical power through various means such as tampering with meters, bypassing meters, tapping directly into power lines, or manipulating billing mechanisms. Analyze here the performance of the proposed IoT-based system for detecting electricity theft. Show the outcomes of the alert system performance. False Positive Rate (FPR): The proportion of legitimate transactions incorrectly identified as theft. False Negative Rate (FNR): The proportion of theft events that were missed by the system. The IoT-based electricity theft detection system is quite efficient. The system's high accuracy, precision, and recall demonstrate its ability to identify and prevent electricity theft effectively.